2019
DOI: 10.3390/cells9010039
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Roles of TIMP-3: Insights into Degenerative Diseases of the Senescent Retina and Brain

Abstract: Tissue inhibitor of metalloproteinase-3 (TIMP-3) is a component of the extracellular environment, where it mediates diverse processes including matrix regulation/turnover, inflammation and angiogenesis. Rare TIMP-3 risk alleles and mutations are directly linked with retinopathies such as age-related macular degeneration (AMD) and Sorsby fundus dystrophy, and potentially, through indirect mechanisms, with Alzheimer's disease. Insights into TIMP-3 activities may be gleaned from studying Sorsby-linked mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 137 publications
0
28
0
Order By: Relevance
“…Although several molecular pathways are involved, such as the accumulation of oxidative products or dysregulation in the vascular and immune system [15] among others, AMD pathophysiology is yet to be fully understood. Using this framework, recent studies have reported that disorders in the regulation of the extracellular matrix (ECM) could play an important role in its etiopathogenesis, as well as its regulator systems, which are composed mainly of the matrix metalloproteinases (MMPs) and the tissue inhibitors of metalloproteinases (TIMPs) [16][17][18][19].…”
Section: Figure 2 (A-f)mentioning
confidence: 99%
See 3 more Smart Citations
“…Although several molecular pathways are involved, such as the accumulation of oxidative products or dysregulation in the vascular and immune system [15] among others, AMD pathophysiology is yet to be fully understood. Using this framework, recent studies have reported that disorders in the regulation of the extracellular matrix (ECM) could play an important role in its etiopathogenesis, as well as its regulator systems, which are composed mainly of the matrix metalloproteinases (MMPs) and the tissue inhibitors of metalloproteinases (TIMPs) [16][17][18][19].…”
Section: Figure 2 (A-f)mentioning
confidence: 99%
“…The involvement of ADAMs by VEGF-A activation in vascular endothelial cells suggests their role in regulating the neovascularization of the retina [79]. The proteolytic ability of MMPs and ADAMs is directly regulated by TIMPs, which bind to them and inhibit their activities [16].…”
Section: Extracellular Matrix In the Eye And The Metalloproteinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The family of TIMP proteins are expressed ubiquitously within the body and play a myriad of biological roles through their ability to reversibly inhibit matrix metalloproteinases (MMPs), a disintegrin and metalloproteinase (ADAMs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) [8,9]. TIMP3 encodes a 24 kDa glycoprotein consisting of two domains: the N-terminal domain is involved in MMP inhibition (and at high levels can induce apoptosis in RPE), whereas the C-terminal domain binds directly to VEGFR2 (KDR), inhibiting VEGF binding and downstream PI3K/Akt and Ras/Raf/ERK signalling in choroidal endothelial cells [1].…”
Section: Introductionmentioning
confidence: 99%